Designing a Multifunctional Separator for High‐Performance Li–S Batteries at Elevated Temperature. Issue 47 (7th October 2019) - He, Yibo; Wu, Shichao; Li, Qi; Zhou, Haoshen
Abstract: The practical applications of lithium–sulfur (Li–S) batteries are seriously limited by the undesirable polysulfide shuttling and lithium dendrite growth. Herein, a multifunctional membrane is designed and prepared by coating a lithiated Nafion (Li@Nafion) layer and an Al2 O3 layer on the two sides of a routine polymer membrane (polypropylene/polyethylene/polypropylene, PEP). The Li@Nafion layer faced to the sulfur cathode builds a "polysulfide‐phobic" surface to restrain the shuttle effect via Coulomb repulsion, while the Al2 O3 layer with a uniform porous structure aids in regulating homogeneous Li + fluxes to achieve stable Li electrodeposition. As a result, the Li//Li symmetric cell with a Li@Nafion/PEP/Al2 O3 (LNPA) separator realizes stable Li plating/striping even after 1000 h at a high current density (5 mA cm −2 ). Moreover, the Li–S batteries incorporating LNPA separators not only can achieve excellent outstanding cyclic stability at an ultrahigh sulfur loading (7.6 mg cm −2 ), but also exhibit impressive electrochemical performance at an elevated temperature (60 °C). The rational design of the LNPA separator presents new insights to develop high‐performance Li–S batteries. Abstract : Polysulfide shuttling and lithium dendrite growth seriously affects electrochemical performance of lithium–sulfur batteries. Coating a Li@Nafion layer on the polypropylene/polyethylene/polypropylene (PEP) membrane effectively prevents polysulfides shuttling via electrostatic repulsion, while introducing an Al2 O3 layer with narrow pore size window between the PEP membrane and Li‐metal anode aids in regulating uniform Li + fluxes to achieve stable Li electrodeposition.